COOP 2016 : proceedings of the 12th International Conference on the Design of Cooperative Systems, 23-27 May 2016, Trento, Italy /: proceedings of the 12th International Conference on the Design of Cooperative Systems, 23-27 May 2016, Trento, Italy. (2016) - Unknown
No abstract available